2021
DOI: 10.3390/agriculture11030192
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Smallholder Farming in Ethiopia and Opportunities by Adopting Climate-Smart Agriculture

Abstract: Agriculture is the backbone of the Ethiopian economy, and the agricultural sector is dominated by smallholder farming systems. The farming systems are facing constraints such as small land size, lack of resources, and increasing degradation of soil quality that hamper sustainable crop production and food security. The effects of climate change (e.g., frequent occurrence of extreme weather events) exacerbate these problems. Applying appropriate technologies like climate-smart agriculture (CSA) can help to resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 147 publications
3
58
0
Order By: Relevance
“…Similarly, Moges and Taye [15] explained this correlation as a positive correlation between farmers' education and cognition, and a high cognitive level can improve the adoption level. Most studies have found that young and highly educated farmers have a higher adoption level, which is similar to our conclusion [1,17,24]. However, some studies have found that demographic variables do not continue to play a role, but depend on the complexity of technology [55].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, Moges and Taye [15] explained this correlation as a positive correlation between farmers' education and cognition, and a high cognitive level can improve the adoption level. Most studies have found that young and highly educated farmers have a higher adoption level, which is similar to our conclusion [1,17,24]. However, some studies have found that demographic variables do not continue to play a role, but depend on the complexity of technology [55].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, we divide the factors into two categories according to different research priorities and some review researches [23]. Some scholars believe that the cognitive differences between farmers and experts on technology will affect the adoption [24][25][26][27]. They believe that the lack of knowledge and skills is a major obstacle to the adoption of this technology, and information dissemination and training are key [26].…”
Section: Introductionmentioning
confidence: 99%
“…Compost was shown to be a suitable amendment considering GHGs and maize yield in our study. However, like mineral fertilizers, compost is also limited in Ethiopia, especially in the area where organic resources are used for another purpose such as fuel, food for animals, or construction material [65,94,95]. As different ratios of compost and mineral fertilizers in the mixtures were found to be suitable to reduce N 2 O and CO 2 emissions and increase maize yield (see Section 4.1), upon the availability of resources, the proportions of these types of fertilizers can be set flexibly in a certain range around 50:50.…”
Section: Mitigation Of Ghg Emissions By Compost Applicationmentioning
confidence: 99%
“…Fertilizer may be preferred for relatively distant fields as these fields may less likely receive organic fertilizer such as manure [4,43]. Indeed, manure (and intercropping) were less practiced on plots located further away from the homestead, as is also documented in other studies [44]. Pests and diseases are also more difficult to control manually when they occur further away from the homestead and pesticides may help in such conditions.…”
Section: • Field Characteristicsmentioning
confidence: 78%